Detection of major viruses infecting shallot and molecular characterization of Onion yellow dwarf virus from several locations in Indonesia - Heri Harti; SRI HENDRASTUTI HIDAYAT; SOBIR; SURYO WIYONO (Society for Indonesian Biodiversity, 2020)
Abstract. Harti H, Hidayat SH, Sobir, Wiyono S. 2020. Detection of major viruses infecting shallot and molecular characterization of Onion yellow dwarf virus from several locations in Indonesia. Biodiversitas 21: 1697-1701. Research was conducted to identify main viruses infecting shallot in several regions in Indonesia and to further characterize genetic variation of Onion yellow dwarf virus (OYDV). Field survey was conducted in Central Java (Brebes), East Java (Probolinggo), West Sumatera (Alahan Panjang), West Nusa Tenggara (Bima), and South Sulawesi (Enrekang). Virus detection from field samples was conducted by dot immunobinding assay. This detection confirmed that infection of OYDV, Shallot yellow stunt virus (SYSV), Shallot latent virus (SLV), and Garlic common latent virus (GarCLV) has occurred in all field with incidence ranged from 20 to 93.5%, 2 to 93%, 21.5 to 80%, and 2 to 80.5%, respectively. The specific primers of Nib gene successfully amplified DNA fragments of OYDV from all locations. Sequencing of DNA fragments revealed that the amplified product was 351 bp. Sequence analysis indicated that the present OYDV isolates from Indonesia shared homology from 82 to 95%; and they had homology from 81 to 95% with OYDV isolates from other countries. The similarity of OYDV isolates from different geographical locations reflected the movements of seed bulbs among and within countries. The phylogenetic tree also revealed that OYDV isolates from different countries did not group together indicating their diverse origin.